Reconsidering law and policy debates : a public health perspective - Culhane, John G. (Cambridge : Cambridge University Press, 2011)
'This book offers fresh approaches to a variety of social and political issues that have become highly polarized and resistant to compromise by examining them through a population-based public health perspective. The topics included are some of the most contentious: abortion and reproductive rights; end-of-life issues, including the right to die and the treatment of pain; the connection between racism and poor health outcomes for African-Americans; the right of same-sex couples to marry; the toll of gun violence and how to reduce it; domestic violence and how the criminal justice model fails to deal with it effectively; and how tort compensation and punitive damages can further public health goals. People at every point along the political spectrum will find the book enlightening and informative. Written by eight authors, all of whom have cross-disciplinary expertise, this book shifts the focus away from the point of view of rights, politics, or morality and examines the effect of laws and policies from the perspective of public health and welfare'--
Machine generated contents note: Part I. Birth and Death: 1. Beyond privacy: a population approach to reproductive rights Wendy E. Parmet; 2. Stretching the boundaries of public health: should end of life care be a public health issue? Diane E. Hoffmann; Part II. The Limits of Civil Rights: 3. Dying while black in America: Maslow's hierarchy of need and racial policy-making Vernellia Randall; 4. Public health and marriage (equality) John G. Culhane; Part III. Dimensions of Violence: 5. Using public health to reform the legal and justice response to domestic violence Evan Stark; 6. Law and policy approaches to keeping guns from high risk people Jon S. Vernick, Daniel W. Webster and Katherine Vittes; Part IV. Beyond Compensation: Public Features of Private Litigation: 7. Tort litigation for the public's health Elizabeth Weeks Leonard; 8. Punitive damages and the public health agenda Jean Macchiaroli Eggen.
Includes bibliographical references and index.
Keywords: Public health laws -- United States; Public health -- Government policy -- United States; Civil rights -- United States; United States -- Social policy